JOB SATISFACTION AS AN OBJECTIVE INDICATOR OF WORK MOTIVATION AMONG INTENSIVE CARE UNIT (ICU) NURSES - Dejan ŽIVANOVIĆ (Rojan GÜMÜŞ, 2019)
Job satisfaction is a complex psychological phenomenon and an extremely important factor of work quality and employees' work motivation. Considering that factors contributing to job (dis)satisfaction also affect work motivation, the level of job satisfaction is used in this psychometric cross-sectional study as an indicator of work motivation among a sample of 71 intensive care units (ICU) nurses in one of universities hospitals in Belgrade, Serbia. The level of job satisfaction was assessed by adapted and customized survey in Serbian language, based on famous Spector's Job Satisfaction Survey (JSS). Analyzing collected data, a high level of job dissatisfaction among participants of our study was founded. Taking into account the high degree of correlation between job satisfaction and work motivation, we concluded that the level of work motivation in the observed sample of ICU nurses was low at the moment of conducting this study, which could point to the existence of serious motivation problems in this field of the nursing profession, even though it is an employee sample from one institution, like in our study.